Direct numerical simulation of a self-similar adverse pressure gradient turbulent boundary layer at the verge of separation. (20th September 2017) - Kitsios, V.; Sekimoto, A.; Atkinson, C.; Sillero, J. A.; Borrell, G.; Gungor, A. G.; Jiménez, J.; Soria, J.
Abstract : The statistical properties are presented for the direct numerical simulation of a self-similar adverse pressure gradient (APG) turbulent boundary layer (TBL) at the verge of separation. The APG TBL has a momentum thickness-based Reynolds number range from Re_[STIX]x1D6FF_2=570 to 13 800, with a self-similar region from Re_[STIX]x1D6FF_2=10 000 to 12 300. Within this domain the average non-dimensional pressure gradient parameter [STIX]x1D6FD=39, where for a unit density [STIX]x1D6FD=[STIX]x1D6FF_1P_\!e^′ /[STIX]x1D70F_w, with [STIX]x1D6FF_1 the displacement thickness, [STIX]x1D70F_w the mean shear stress at the wall and P_\!e^′ the far-field pressure gradient. This flow is compared with previous zero pressure gradient and mild APG TBL ( [STIX]x1D6FD=1 ) results of similar Reynolds number. All flows are generated via the direct numerical simulation of a TBL on a flat surface with far-field boundary conditions tailored to apply the desired pressure gradient. The conditions for self-similarity, and the appropriate length and velocity scales, are derived. The mean and Reynolds stress profiles are shown to collapse when non-dimensionalised on the basis of these length and velocity scales. As the pressure gradient increases, the extent of the wake region in the mean streamwise velocity profiles increases, whilst the extent of the log-layer and viscous sublayer decreases. The Reynolds stress, production and dissipation profiles of the APG TBL cases exhibit a second outer peak, which becomes more pronounced and more spatially localised with increasing pressure gradient. This outer peak is located at the point of inflection of the mean velocity profiles, and is suggestive of the presence of a shear flow instability. The maximum streamwise velocity variance is located at a wall normal position of [STIX]x1D6FF_1 of spanwise wavelength of 2[STIX]x1D6FF_1 . In summary as the pressure gradient increases the flow has properties less like a zero pressure gradient TBL and more akin to a free shear layer.